Klimaet i ministeriet. Udviklingen af den første danske klimapolitik, ca. 1980-1992 - Jensen, Niklas Thode (Historisk Tidsskrift, 2025)
Climate issues first appeared on Danish ministerial agendas after the release of the UN’s Brundtland Report in August 1987. Hence, Denmark was generally in a position of following rather than leading on this issue internationally. However, a few Danish researchers had highlighted the issue earlier in the 1980s, and they became part of a small group of experts who played a role as catalysts and advisors while a Danish climate policy was developed. One reason for their influence was the rapid expansion of scientific knowledge about climate issues. The Ministry of Environment consciously used the emerging climate agenda to leverage its influence over the purviews of other ministries, quickly becoming the most powerful actor. Formally, the Danish government’s Action Plan for Environment and Development (1989) and Energi 2000 (1990), the energy action plan, were developed in collaboration with not only ministries and scientific advisors but also industry, labour unions, environmental organisations, and NGOs, yet the Ministry of Environment’s preferences are present throughout. At least one central scientific institution repeatedly opposed the Ministry of Environment’s approach, namely, the Danish Meteorological Institute (DMI). The disagreement stemmed from the fact that climate change due to human emissions of greenhouse gases had only been suggested by climate models, not definitively proven. DMI took the classic scientific stance that models should not form the basis for comprehensive measures before observations confirmed their predictions, while the Ministry of Environment adhered to the precautionary principle. The Ministry of Environment’s position came to define both Danish climate policy and climate research strategy, which supported research on the impacts and prevention of climate change over model-based research. Thus, the prevailing approach and logic of the Ministry of Environment and environmental researchers were transferred from the environmental sector to the climate sector.